Comparative studies of the anti-leishmanial activity of three Crotalus durissus ssp venoms - Passero, L. F. D.; Tomokane, T. Y.; Corbett, C. E. P.; Laurenti, M. D.; Toyama, M. H. (Springer, 2007)
In this study, we compared the anti-leishmanial activity of three crotalic venoms (Crotalus durissus terrificus-Cdt, Crotalus durissus cascavella-Cdca, and Crotalus durissus collilineatus-Cdcol). Different concentrations of each venom incubated with Leishmania (Leishmania) amazonensis promastigotes were used. Cdt venom exhibited a higher anti-leishmanial activity (Inhibitory concentration-IC50-value of 4.70 +/- 1.72 mu g/ml) in comparison with that of Cdca venom (IC50 value of 9.41 +/- 1.21 mu g/ml), while Cdcol venom increased parasite numbers in 50% at a concentration of 44.30 +/- 2.18 mu g/ml. In addition, this venom showed a low anti-leishmanial activity in higher concentrations (IC50 value of 281.00 +/- 9.50 mu g/ml). The main fractions of Cdca venom were isolated and assayed under similar conditions used for assessing crude venom. The most active fractions were gyroxin and crotamine that had IC50 values of 3.80 +/- 0.52 mu g/ml and 19.95 +/- 4.21 mu g/ml, respectively. Convulxin also inhibited parasite growth rate, although this effect was not dose-dependent. Crotoxin was the least effective fraction with an IC50 value of 99.80 +/- 2.21 mu g/ml. None of the protein fractions presented cytotoxic effects against J774 cells in culture. In vivo assays using BALB/c mice revealed that crotoxin and crotamine were the main toxic fractions. In conclusion, C. durissus cascavella venom has three main fractions with anti-leishmanial activity. These results open new possibilities to find proteins that might be used as possible agents against cutaneous leishmaniasis.